Understanding Dropout Dynamics of TVET Students: A Case of Apprenticeship Model in Nepal - Acharya, Rakshya (Journal of Technical and Vocational Education and Training, 2026)
The dual-VET apprenticeship model is considered as an improved model of technical and vocational education and training (TVET) that enhances a higher possibility of ensuring a rewarding job. Such model provides dual benefits. On the one hand, it helps trainees achieve high employability and, on the other hand, the employers get skilled and loyal workforce to their industries. Despite sound theoretical base of this modality, the practice shows low retention rate in Nepal and many trainees drop out from the program in the middle. This study seeks to understand the dynamics of dropout phenomenon via apprentices’ dropout experiences. It basically adopts a qualitative approach. However, it first assesses the prevalence and distribution of such dropout event of apprentices quantitatively to problematize the issue. Then, in-depth interviews with five dropouts and two FGDs with current apprentices draw qualitative information to enrich the study. This study portrays three major findings: a) The dropout phenomenon starts right from the selection process of apprentices, b) The apprentices consider this program as a program to pursue their short-term interest, and c) There is a mismatch between apprentices’ expectation and field realities. In sum, the occurrence of dropout of apprentices was the result of less informed choice, lack of counseling during the program, and institutional arrangements of TVET system where the ground realities were interwoven with socio-cultural and economic background of apprentices. The dropout phenomenon is explained under the social cognitive career theory. One of the major contributions of this study will be identifying policy-practice gaps in implementing the apprenticeship model of TVET. Moreover, the findings will be helpful to understand and improve the working strategies in undergoing TVET programs and projects in the local context of Nepal.